The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.12988/ams.2014.44267
|View full text |Cite
|
Sign up to set email alerts
|

Exponentiated generalized inverse Weibull distribution

Abstract: The inverse Weibull distribution can be readily applied to a wide range of situations including applications in medicine, reliability and ecology. In this article we introduce a new model of generalized inverse Weibull distribution referred to as the Exponentiated generalized inverse distribution. We provide a comprehensive mathematical treatment of this distribution. We derive the moment generating function and the rth moment thus generalizing some results in the literature. Expressions for the density, momen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…On the basis of this fact, several models were proposed to model bathtub‐shaped failure rates from the very beginning, which apply a variety of methods for estimating and testing including the method of moments, least squares, and maximum likelihood . Comprehensive overviews of bathtub‐shaped failure rate functions are provided by Rajarshi and Rajarshi and Lai et al Models that present bathtub‐shaped failure rates are also extremely useful in survival analysis . Much research has been carried out recently with the aim of serving the needs of reliability engineers and practitioners, most of them presenting new lifetime distributions that have bathtub‐shaped failure rate functions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of this fact, several models were proposed to model bathtub‐shaped failure rates from the very beginning, which apply a variety of methods for estimating and testing including the method of moments, least squares, and maximum likelihood . Comprehensive overviews of bathtub‐shaped failure rate functions are provided by Rajarshi and Rajarshi and Lai et al Models that present bathtub‐shaped failure rates are also extremely useful in survival analysis . Much research has been carried out recently with the aim of serving the needs of reliability engineers and practitioners, most of them presenting new lifetime distributions that have bathtub‐shaped failure rate functions .…”
Section: Introductionmentioning
confidence: 99%
“…7,8,[10][11][12][13][14] Comprehensive overviews of bathtub-shaped failure rate functions are provided by Rajarshi and Rajarshi 8 and Lai et al 15 Models that present bathtub-shaped failure rates are also extremely useful in survival analysis. 16 Much research has been carried out recently with the aim of serving the needs of reliability engineers and practitioners, most of them presenting new lifetime distributions that have bathtub-shaped failure rate functions. 17 To satisfy all these needs, the Weibull distributions have also been proven to be very flexible in modeling various types of lifetime distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Then, by using the exponential expansion for the last term in (6) and further the binomial expansion for a positive real power yields…”
Section: Expansion For Densities Of Oge-iw Distributionmentioning
confidence: 99%
“…Shahbaz et al (2012) suggested the Kumaraswamy inverse Weibull distribution. Elbatal and Muhammed (2014) introduced the exponentiated generalized inverse Weibull distribution. The generalized inverse Weibull distribution including the exponentiated or proportional reverse hazard and Kumaraswamy generalized inverse Weibull distributions have been suggested by Oluyede and Yang (2014).…”
Section: Introductionmentioning
confidence: 99%
“…We refer to the papers: Lemonte, A. J., 2014;Elbatal, I. & Muhammed, H. Z., 2014;Moors, 1988;Da Silva, et al, 2015;De Andrade, et al, 2015;Bourguignon, M., et al, 2015;Mansoor, M., et al, 2016;Arya, G.& Elbata, I., 2015 ;Silva, A. O., et al, 2015), which used the EG class to extend the Burr III, Birnbaum-Saunders, inverse Weibull, inverted exponential, generalized gamma, Gumbel, extended exponential, Fréchet, modified Weibull and Dagum distributions, respectively.…”
Section: Introductionmentioning
confidence: 99%